InnoScape: a creative artificial ecosystem model of innovation and boundary processes in epistemic communities. (17th October 2012) - Zou, G.; Yilmaz, L.
As the science enterprise becomes increasingly complex and interdisciplinary, implementing policies that foster collective creativity for science-based innovation emerges as a critical issue. In this paper, we introduce a general-purpose model to study dynamic processes of collective creativity in scientific communities. An exploratory study based on agent simulation is conducted to better understand how innovation capacity and sustainability of the innovation ecosystem relate to interaction topologies, culture and resource allocation strategies. Experimental results indicate that communities, by building highly connected clusters under low to moderate resource availability, can produce epistemic cultures with high degrees of sustainability. Additionally, priority-based investment coupled with technology transferring improves diversity within the science-based innovation ecosystem.